Gentamicin encapsulated within a biopolymer for the treatment of Staphylococcus aureus and Escherichia coli infected skin ulcers - Gemeinder, José Lúcio Pádua [UNESP]; Barros, Natan Roberto de [UNESP]; Pegorin, Giovana Sant’Ana [UNESP]; Singulani, Junya de Lacorte [UNESP]; Borges, Felipe Azevedo [UNESP]; Arco, Marina Constante Gabriel Del; Giannini, Maria José Soares Mendes [UNESP]; Almeida, Ana Marisa Fusco [UNESP]; Salvador, Sérgio Luiz de Souza; Herculano, Rondinelli Donizetti [UNESP] (My University, 2020)
Skin wound infection requires carefully long-term treatment with an immense financial burden to healthcare systems worldwide. Various strategies such as drug delivery systems using polymer matrix from natural source have been used to enhance wound healing. Natural rubber latex (NRL) from Hevea brasiliensis has shown angiogenic and tissue repair properties. Gentamicin sulfate (GS) is a broad-spectrum antibiotic which inhibits the growth of a wide variety of microorganisms and, because of this, it has also been applied topically for treatment of local infections. The aim of this study was to develop a GS release system using NRL as matrix for Staphylococcus aureus and Escherichia coli infected skin ulcers treatment, without changing drug antibiotic properties. The matrix did not change the GS antimicrobial activity against S. aureus and E. coli strains. Moreover, the NRL-GS biomembrane did not exhibit hemolytic activity, being non-toxic to red blood cells. The eluates of NRL-GS biomembranes and GS solutions did not significantly reduce the survival of Caenorhabditis elegans worms for 24 h at any of the tested concentrations. Thus, these results emphasize that the NRL-GS biomembrane proved to be a promising biomaterial for future studies on the development of dressings for topical uses, inexpensive and practicable, keeping drug antibiotic properties against pathogens and to reduce the side effects.
Keywords: antimicrobial activity; Biomembrane; Caenorhabditis elegans; dressing; gentamicin; hemolysis